Persistent extreme ultraviolet irradiance in Antarctica despite the ozone recovery onset - Cordero, Raul R.; Feron, Sarah; Damiani, Alessandro; Redondas, Alberto; Carrasco Cerda, Jorge Fernando; Sepulveda, Edgardo; Jorquera, Jose; Fernandoy, Francisco; Llanillo, Pedro; Rowe, Penny M.; Seckmeyer, Gunther (My University, 2022)
Attributable to the Montreal Protocol, the most successful environmental treaty ever, human-made ozone-depleting substances are declining and the stratospheric Antarctic ozone layer is recovering. However, the Antarctic ozone hole continues to occur every year, with the severity of ozone loss strongly modulated by meteorological conditions. In late November and early December 2020, we measured at the northern tip of the Antarctic Peninsula the highest ultraviolet (UV) irradiances recorded in the Antarctic continent in more than two decades. On Dec. 2nd, the noon-time UV index on King George Island peaked at 14.3, very close to the largest UV index ever recorded in the continent. On Dec. 3rd, the erythemal daily dose at the same site was among the highest on Earth, only comparable to those recorded at high altitude sites in the Atacama Desert, near the Tropic of Capricorn. Here we show that, despite the Antarctic ozone recovery observed in early spring, the conditions that favor these extreme surface UV events persist in late spring, when the biologically effective UV radiation is more consequential. These conditions include long-lasting ozone holes (attributable to the polar vortex dynamics) that often bring ozone-depleted air over the Antarctic Peninsula in late spring. The fact that these conditions have been occurring at about the same frequency during the last two decades explains the persistence of extreme surface UV events in Antarctica.
Keywords: Ozone Depletion; Montreal Protocol; Peninsula